2007
DOI: 10.1139/h06-092
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of metabolically obese normal-weight (MONW) subjects

Abstract: The existence of a subgroup of normal-weight individuals displaying obesity-related phenotypic characteristics was first proposed in 1981. These individuals were identified as metabolically obese but normal weight (MONW). It was hypothesized that these individuals might be characterized by hyperinsulinemia and (or) insulin resistance, as well as by hypertriglyceridemia and high blood pressure despite having a body mass index (BMI) < 25 kg/m2. Such characteristics could confer upon MONW subjects a higher cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
138
1
17

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(170 citation statements)
references
References 39 publications
14
138
1
17
Order By: Relevance
“…Increased visceral obesity (as opposed to general obesity), high fructose and fat intake and genetic risk factors, includ ing congenital defects of metabolism, might be associ ated with lean NAFLD. A very large proportion of lean NAFLD cases probably belong to the 'metabolically obese, normal weight' pheno type 79 , described in at least 5% of the popu lation in the West. This subgroup comprises individuals who are non obese, frequently sedentary, and who have impaired insulin sensitivity, increased cardio vascular risk and increased liver lipid levels, the consequence of decreased capacity for storing fat and reduced mitochon drial function in adipose tissue and increased hepatic de novo lipogenesis 79 .…”
Section: Incidence Of Nafld and Future Projections In Europementioning
confidence: 99%
“…Increased visceral obesity (as opposed to general obesity), high fructose and fat intake and genetic risk factors, includ ing congenital defects of metabolism, might be associ ated with lean NAFLD. A very large proportion of lean NAFLD cases probably belong to the 'metabolically obese, normal weight' pheno type 79 , described in at least 5% of the popu lation in the West. This subgroup comprises individuals who are non obese, frequently sedentary, and who have impaired insulin sensitivity, increased cardio vascular risk and increased liver lipid levels, the consequence of decreased capacity for storing fat and reduced mitochon drial function in adipose tissue and increased hepatic de novo lipogenesis 79 .…”
Section: Incidence Of Nafld and Future Projections In Europementioning
confidence: 99%
“…1 However, we and others [2][3][4][5][6] have documented the presence of both insulin-resistant normal-weight participants and obese individuals who are insulin sensitive despite their obesity. These studies highlight the wide interindividual differences in insulin sensitivity that exists for any given amount of body fat, suggesting that additional factors modulate insulin action.…”
Section: Introductionmentioning
confidence: 79%
“…31 Investigation of metabolically obese normal-weight and lipodystrophic participants showed that even in individuals with low total fat, alteration of the ratio was associated with deteriorated insulin sensitivity. 4,32 In type 2 diabetics, thiazolidinedione improved glucose control despite significant weight gain. 33 Importantly, fat incretion occurred mostly in peripheral subcutaneous adipose tissue, often in the absence of any changes in visceral mass, resulting in a more favorable PFM/CFM ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these data do not apply to lesser degrees of overweight or normal weight individuals, though others have shown that increasing abdominal obesity predicts insulin resistance even in normal weight individuals. 44 We specifically included overweight and obese individuals because the prevalence of being overweight (BMI 425 kg m -1 ) in patients with established CHD is 80% and the prevalence of obesity (BMI430 kg m -1 ) is 40%, 19,20 which is considerably greater than the general American adult population (64 and 30%, respectively). 45 Third limitation is that the data were only taken with subjects taking their usual preventive medications.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that 25 of the 74 patients had a fasting glucose of 100-126 mg per 100 ml. The mean age was 64±9 years (range 44-84 years, median 63 years) and all patients had a BMI of X27 kg m -2 (mean 32 ± 4, range [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. All the women were postmenopausal and none were taking hormone replacement therapy.…”
Section: Methodsmentioning
confidence: 99%